THE NEW-OLD COSMOLOGY - Otto E. Rossler (European Scientific Journal, ESJ, 2013)
The recently discovered physics discipline of cryodynamics, sister discipline to thermodynamics, enables a new picture of the cosmos. A stationary, infinite, eternal, fractal cosmos that can be called the Clifford-Zwicky-Mandelbrot (CZM) cosmos emerges. Many elements of the currently accepted cosmology are put up for replacement in a 12-point list.